The rise and fall of mass taxation in Uganda 1900 - 2005 - Ole Therkildsen (Danish Institute for International Studies (DIIS), 2006)
Although Graduated Personal Tax (GPT) paid to local government in Uganda has caused numerous tax riots throughout the past century, it is only since the mid-1990s that competitive presidential elections have provided people with an effective way to express their dissatisfaction with it. Thus, greater political competition was instrumental in almost dismantling the GPT in 2001 and abolished in 2005. Positive governance effects will follow from this. As shown by the comparison of taxpayer rights and enforcement practices (in particular the use of imprisonment) for GPT and income tax paid to central government, the former has been collected with the use of much more coercion than the latter. Coercive approaches to taxation become more difficult to sustain with greater political competition.
Keywords: 330; Personalsteuer; Einkommensteuer; Uganda